Tourist's Reference on Digital Information Technology in Intramuros - Calfoforo, Chariz Nicole C.; Lastimosa, Gleen S.; Lim Jr.; Juanito M.; and Palaganas, Herlito M. 4 0 16; 5
ABSTRACT: The study aims to assess the level of preference of tourist in digital information technology for disseminating information about the tourists spot in Intramuros without neglecting its Historical and Cultural essence in the place. The study used the Descriptive-Correlational Method of a research designs or the study addresses the what questions in regards to the variable that are being studied. The study was supported and directed by a survey questionnaire that will aid as an instrument in determining the research output. The survey questionnaire was divided into two parts. The first part is about the independent variable that shows the tourists profile that visits Intramuros according to their age, educational attainment and nationality. The second part is consists of the dependent variables of the study showing the different digital information technology use for information dissemination as for preference of tourists. The statistical analysis used the following statistical tools to answer specific questions. For research question part 1, the researchers identified the tourists profile in Intramuros and further analyse the data applying the frequency and percentage distribution. For research question no. 2 the researchers identified the level of acceptability of Digital Information Technology infusion in Intramuros through the preference of the tourists. The researchers use the rank system to apply the preference of the respondents on the four (4) selected digital information technologies. The researchers had concluded that the mobile application as the most preferred technology for the information dissemination inside Intramuros a survey using the Likert Scale. With the conclusion of the researchers the recommendations formulated are the participation of the Department of Tourism, the City Government of Manila and the Intramuros Administration for the creation of the said mobile application for Intramuros. The said software will give the necessary information, events, directions, accomodations, restaurants, establishment and special activities inside Intramuros. Also the participation of the local community is highly recommended for the promotion of the said software.
Thesis (B.S. in Travel and Tourism Management) - Pamantasan ng Lungsod ng Maynila, 2015.
Keywords: 2 -- 0; 6; 20; 20; 2